Acute Stroke Management in Türkiye: Intravenous Tissue Plasminogen Activator and Thrombectomy NöroTek: Türkiye Neurology Single Day Study - Mehmet Akif Topçuoğlu; Atilla Özcan Özdemir; Ethem Murat Arsava; Aygül Güneş; Özlem Aykaç; Elif Sarıönder Gencer; Murat Çabalar; Vildan Yayla; Hacı Ali Erdoğan; Mücahid Erdoğan; Zeynep Özdemir Acar; Semih Giray; et al. (Türk Nöroloji Dergisi, 2023)
Objective: To reveal the profile and practice in patients with acute stroke who received intravenous tissue plasminogen activator (IV tPA) and/or neuro-interventional therapy in Türkiye. Materials and Methods: On World Stroke Awareness Day, May 10, 2018, 1,790 patients hospitalized in 87 neurology units spread over 30 health regions were evaluated retrospectively and prospectively. Results: Intravenous tPA was administered to 12% of 859 cases of acute ischemic stroke in 45 units participating in the study. In the same period, 8.3% of the cases received neurointerventional treatment. The rate of good prognosis [modified Rankin score (mRS) 0–2] at discharge was 46% in 83 patients who received only IV tPA [age: 67 +- 12 years; National Institutes of Health Stroke Scale (NIHSS): 12 +- 6; hospital stay, 24 +- 29 days]; 35% in 51 patients who underwent thrombectomy (MT) alone (age: 64 +- 13 years; NIHSS: 14.1 +- 6.5; length of hospital stay, 33 +- 31 days), 19% in those who received combined treatment (age: 66 +- 14 years; NIHSS: 15.6 +- 5.4; length of hospital stay, 26 +- 35 days), and 56% of 695 patients who did not receive treatment for revascularization (age: 70 +- 13 years; NIHSS: 7.6 +- 7.2; length of hospital stay, 21 +- 28 days). The symptom-to-door time was 87 +- 53 minutes in the IV treatment group and 200 +- 26 minutes in the neurointerventional group. The average door-to-needle time was 66 +- 49 minutes in the IV tPA group. In the neurothrombectomy group, the door-to-groin time was 103 +- 90 minutes, and the TICI 2b-3 rate was 70.3%. In 103 patients who received IV tPA, the discharge mRS 0–2 was 41%, while the rate of mRS 0–1 was 28%. In 71 patients who underwent neurothrombectomy, the mRS 0–2 was 31% and mRS 0–1 was 18%. The door-to-groin time was approximately 30 minutes longer if IV tPA was received (125 +- 107 and 95 +- 83 minutes, respectively). Symptomatic bleeding rates were 4.8% in IV recipients, 17.6% among those who received only MT, and 15% in combined therapy. Globally, the hemorrhage rate was 6.8% in patients receiving IV tPA and 16.9% in MT. Conclusion: IV thrombolytic and neurointerventional treatment applications in acute ischemic stroke in Türkiye can provide the anticipated results. Heterogeneity has begun to be reduced in our country with the dissemination of the system indicated by the 'Directive on Health Services to be Provided to Patients with Acute Stroke.'